2012
DOI: 10.1089/hyb.2011.0102
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of an IgE-Class Monoclonal Antibody Specific for the Bullous Pemphigoid Autoantigen, BP180

Abstract: BP180 (collagen XVII) is the target antigen in several autoimmune diseases including bullous pemphigoid (BP). Both IgE and IgG class autoantibodies have been shown to be pathogenic in BP; however, studies designed to elucidate the patho-mechanisms mediated specifically by the IgE-class autoantibodies are limited by the low levels (ng/mL) of IgE in human sera. In this report, we developed mouse IgE class monoclonal antibodies (MAbs) against the immunodominant NC16A domain of the human BP180 protein and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…As for the IgG isotype, serum levels of anti‐BP180 NC16A IgE were correlated with disease activity and disappearance of these antibodies was associated with clinical remission . The pathogenicity of specific anti‐BP180 IgE has been proven by several in vitro experiments and by in vivo mouse models . Similarly, the therapeutic benefits brought by the selective suppression of the IgE activity by omalizumab, in BP patients resistant to corticotherapy, are also an argument for the IgE pathogenicity …”
Section: Bp‐related Autoantibodies As Biomarkers Of Bp Diseasementioning
confidence: 97%
“…As for the IgG isotype, serum levels of anti‐BP180 NC16A IgE were correlated with disease activity and disappearance of these antibodies was associated with clinical remission . The pathogenicity of specific anti‐BP180 IgE has been proven by several in vitro experiments and by in vivo mouse models . Similarly, the therapeutic benefits brought by the selective suppression of the IgE activity by omalizumab, in BP patients resistant to corticotherapy, are also an argument for the IgE pathogenicity …”
Section: Bp‐related Autoantibodies As Biomarkers Of Bp Diseasementioning
confidence: 97%
“…[20,[115][116][117] The secretion from cultured keratinocytes was also seen in response to incubation with a monoclonal antihuman BP180 NC16A IgE. [114] Furthermore, incubation of keratinocytes with anti-BP180 IgE led to internalization of BP180. [118] Both effects have previously been shown for IgG-anti BP180 antibodies.…”
Section: Pathogenic Relevance Of Ige Anti-bp180 Antibodiesmentioning
confidence: 99%
“…In the first approach, the effect of anti-BP180 IgE was investigated in vitro. Incubation of cultured human keratinocytes with IgE isolated from BP sera resulted in the release of IL-6 and IL-8, [113,114] two cytokines that may mediate disease development in BP, e.g. by the attraction of inflammatory cells.…”
Section: Pathogenic Relevance Of Ige Anti-bp180 Antibodiesmentioning
confidence: 99%
“…13 A study of an SLE cohort that included patients from France and the United States revealed the presence of self-reactive IgE against at least 7 autoantigens, for which 65% of the subjects presented IgE autoantibodies to 1 or more of them (Table I). 4,5,[14][15][16][17][18][19][20][21][22][23][24][25][26] The prevalence was even greater within the subgroup of patients with active disease (83%). Levels of IgE specific for double-stranded DNA (dsDNA) showed the most significant association with disease activity and hypocomplementemia.…”
Section: Prevalence and Specificities Of Ige Autoantibodies In Patienmentioning
confidence: 99%